Imogene's antlers - Small, David, 1945- (New York : Crown, 1985)
One Thursday, Imogene wakes up with a pair of antlers growing out of her head and causes a sensation wherever she goes.
Wilson's Children
Elem. School Library Collection
School Library Journal
3.0
K-3
Keywords: Children's stories, American; Antlers -- Fiction; Humorous stories; Antlers -- Fiction; Humorous fiction